Гарантія незалежності суддів та їх реалізація в сучасній Україні - Галайденко, Тетяна Василівна; Галайденко, Татьяна Васильевна; Galaidenko, Tatiana V. (My University, 2013)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.10 - судоустрій; прокуратура та адвокатура. - Національний університет «Одеська юридична академія», Одеса, 2013. Дисертацію присвячено комплексному дослідженню гарантій незалежності суддів як важливого правового інституту судової влади, невід'ємної частини статусу суддів. Розглянуто поняття і зміст незалежності суддів щодо їх прав і обов'язків вільно, неупереджено і справедливо розглядати справи за своїм внутрішнім переконанням на підставі закону без стороннього впливу для ефективного захисту прав людини та інтересів держави. Проаналізовано сучасний стан незалежності суддів і характер його оцінки у громадській думці, а також значення документів Європейського співтовариства для удосконалення законодавства про статус суддів. Розглянуто зміст особливих професійних, соціально-економічних, процесуальних гарантій незалежності суддів, а також гарантій безпеки суддів і членів їхніх сімей від злочинних посягань. Розкрито зміст суддівського розсуду та його значення для забезпечення незалежності суддів, особливості застосування принципу таємниці нарадчої кімнати стосовно одноосібного і колегіального розгляду справ. Запропоновано зосередити гарантії безпеки суддів і членів їх сімей в окремій главі Закону України «Про судоустрій і статус суддів». Проаналізовано роль органів законодавчої влади, Президента України, органів прокуратури і суддівського самоврядування у забезпеченні незалежності суддів.

Диссертация на соискание ученой степени кандидата юридических наук по специальности 12.00.10 - судоустройство; прокуратура и адвокатура. - Национальный университет «Одесская юридическая академия», Одесса, 2013. Диссертация посвящена комплексному исследованию гарантий независимости судей как важного правового института судебной власти, неотъемлемой части статуса судей. Рассмотрены понятие и содержание независимости судей относительно их прав и обязанностей свободно, беспристрастно и справедливо рассматривать дела по своему внутреннему убеждению на основании закона без постороннего воздействия для эффективной защиты прав человека и интересов государства. Проанализировано современное состояние независимости судей и характер его оценки в общественном мнении, а также значение документов Европейского сообщества для совершенствования законодательства о статусе судей. Рассмотрено содержание особых профессиональных, социально- экономических, процессуальных гарантий независимости судей, а также гарантий безопасности судей и членов их семей от преступных посягательств. Раскрыто содержание судейского усмотрения и его значение для обеспечения независимости судей, особенности применения принципа тайны совещательной комнаты по единоличного и коллегиального рассмотрения дел. Предложено сосредоточить обеспечение безопасности судей и членов их семей в отдельной главе Закона Украины «О судоустройстве и статусе судей». Проанализирована роль органов законодательной власти, Президента Украины, органов прокуратуры и судейского самоуправления в обеспечении независимости судей.

Thesis for the scientific degree of candidate of legal sciences, specialty 12.00.10 - judicial system, public prosecutors and lawyers - National University «Odesa Law Academy», Odessa, 2013. Thesis is devoted to the complex research of guarantees of the independence of judges as an important legal institution of the judiciary and an integral part of the judiciary. The concept of the content and status of judges are considered as to their rights and obligations to investigate the case freely, fairly and impartially on their own inner convictions on the basis of the law without outside influence for the effective protection of human rights and the interests of the state. The author analyzes the current state of judicial independence, the factors that have a positive or negative impact on the situation in this sphere, the processes of the formation of public opinion on the assessment of the authority of courts and judges. The regulatory and other documents of European institutions have been analyzed in regard to the judicial independence and embodiments of their recommendations in Ukraine. The notion of a guarantee of the independence of judges has been formed as provided by the Constitution and laws of Ukraine, mechanisms of action of the principle of judicial independence and the elimination or minimization of the circumstances preventing the independent performance of professional judges and jury duty for the implementation of justice. In this regard personal, social and economic, procedural guarantees for judges, guarantees of safety of judges and members of their families are allocated. Guarantees have a state domineering character, except for internal belief (imperative) of the judge, ready 'to protect the independence of illegal intervention in judicial activity. It is proved that real social and economic guarantees of independence of judges do not only stimulate a fair execution of their duty requires, but also are a confirmation of high authority of the judge in society, and also serve as a limiting factor against corruption. The procedural guarantees of the independence of judges is proposed to allocate in a separate list. Particular attention is paid to such procedural safeguards as judicial discretion and secrecy of the deliberations room. Judicial discretion is defined as a personal conviction of the judge on the content of the judgment of the rule of law, justice and fairness on the basis of the analysis of the evidence in the case and the professional interpretation of the legislation. The features of a secret deliberation room in individual or peer review cases are also allocated. It is the role of the legislature and the President to ensure the independence of judges in areas of law-making and enforcement and the role of judicial self- government in the protection of judges from illegal interference in their activities. It is proposed to include regulations concerning the safety of judges and their families, directly to the Law of Ukraine «On the Judicial System and Status of Judges», as well as to restructure the system of courts and to ensure due process in judicial proceedings.
Галайденко Т. В. Гарантія незалежності суддів та їх реалізація в сучасній Україні : автореф. дис. ... канд. юрид. наук : 12.00.10 / Т. В. Галайденко; кер. роботи В. В. Долежан; Нац. ун.-т "Одеська юридична академія". – Одеса, 2013. – 20 с.
Keywords: незалежність суддів; гарантії незалежності суддів; суддівський розсуд; відповідальність за порушення принципу незалежності суддів; органи суддівського самоврядування; независимость судей; гарантии независимости судей; судейское усмотрение; ответственность за нарушение принципа независимости судей; органы судейского самоуправления; independence of the judiciary; guarantees of the independence of the judiciary; judicial discretion; responsibility for violations of the principle of judicial independence; judicial self-government bodies